Pengaruh User Experience dan Consumer-Based Brand Equity Terhadap Loyalitas Pengguna Shopee - Hoiriyah Hoiriyah; Darmansah Darmansah; Muhammad Eka Purbaya (JURIKOM (Jurnal Riset Komputer), 2022)
Shopee can be regarded as an E-Marketplace which is the second wave of E-Commerce and expands the combination of consumer business (B2B, C2B, and C2C) into B2B. Shopee is a phenomenon that occurs and will continue to grow in the years to come. However, it is felt that changing trends and moving application users occur very quickly. Every user must pay attention to the advantages and disadvantages of the application used. User requests on the application can be seen in terms of user behavior. The level of comfort felt by users in using the application can be measured through user behavior factors. Through user behavior factors emerge user experiences arising from interactions with the application. The purpose of this study is to determine the factors that influence between variables by identifying the relationship between endogenous and exogenous variables on Brand Loyalty by using the modified User Experience and Consumer Based Brand Equity methods. Respondents in the questionnaire were 150 using non-probability sampling technique with purposive sampling type, data analysis using Structural Equation Modeling-Partial Last Square with a Likert scale as the measurement scale used. The result of this research is that Brand Association (BA) is not significant positive on Brand Loyalty (BL). Brand Trust (BT) is significantly positive on Brand Loyalty (BL). Perceived Value (PV) is significantly positive on Brand Loyalty (BL). Pleasure in Use (PiU) is significantly positive on Brand Loyalty (BL). Social Value (SV) is significantly positive on Brand Loyalty (BL). Usability (US) is not significant positive towards Brand Loyalty (BL)